Functional Results of a Modified Extracorporeal Septoplasty With Open Access. Issue 1 (July 2018) - Marangi, Giovanni Francesco; Segreto, Francesco; Signoretti, Matteo; Cazzato, Vito; Persichetti, Paolo
Abstract : Background: Nasal septal deviation is one of the major causes of nasal respiratory flow disorders. During the rhinoseptoplasty, the septum can be treated through a closed traditional access or through an open access. To date, there are still no objective functional indications of the best access to use in rhinoseptoplasty. For this reason, we evaluated, objectively and subjectively, the functional efficiency of open access and compared it with that of closed access. The aim is to highlight any functional outcome differences between the 2 types of access. Methods: The study involved up to 50 patients, from January 2006 to June 2017; 20 patients underwent modified extracorporeal rhinoseptoplasty with open access, and 30 patients underwent modified extracorporeal rhinoseptoplasty with closed access. We evaluated the nasal obstruction by using the validated questionnaire Nasal Obstruction Symptoms Evaluation (subjective method) and by performing the anterior active rhinomanometry (objective method). Both evaluations were performed in 3 different times: preoperative period, 3 months, and 6 months after surgery. Results: In the open cohort, the rhinomanometric analysis showed a statistically significant increase between preoperative period and sixth month after surgery; however, the nose score had a statistically significant increase in both 3 and 6 months after surgery. At 3 months after surgery, the rhinomanometric score was higher in patients with closed access than patients with open access; this difference has disappeared at 6 months after surgery. At 3 and 6 months after surgery, the improvement in the Nasal Obstruction Symptoms Evaluation average score was greater in patients with open access compared with patients with closed access. No complications were observed. Conclusions: Based on the results obtained from our work, we can declare that open access is a functionally valid procedure. At 6 months after surgery, the 2 accesses have a comparable functional efficacy.